Sensing of acetone vapor by flame-made Sn/ZnO nanoparticles - K. Wetchakun (2018)
Pure ZnO and Sn-doped ZnO nanoparticles were synthesized using flame spray pyrolysis technique. Precursor solutions (0.5 M) were prepared by dissolving the appropriate amounts of zinc naphthenate and tin (II) 2-ethylhexanoate in xylene. The nanopowders were characterized by X-ray diffraction (XRD), brunauer Emmett, and teller (BET), and transmission electron microscopy (TEM) techniques. The sensing films were prepared by spin coating. The response of gas sensors were tested during backward cycle under exposure acetone vapor (25-400 ppm) at operating temperatures ranging from 200-400°C. The cross-section and films morphology were further characterized by field emission scanning electron microscopy-energy dispersive spectroscopy (FESEM-EDS) techniques. It was found that 3 at.% Sn-doped ZnO sensor showed the best sensing performance towards acetone in terms of the highest response and fastest response times within a few minutes. Copyright © 2011 American Scientific Publishers.